ANALISIS OPTIMALISASI PENGELOLAAN ASET DI KEPOLISIAN DAERAH DAERAH ISTIMEWA YOGYAKA - , Cahyani, S.E., Dra. Wahyu Hidayati, M.Si. ([Yogyakarta] : Universitas Gadjah Mada, 2011)
This study is about optimizing the analysis of asset management at Regional Police, the Special Region of Yogyakarta. Objectives to be achieved in this study are as follows: (1) To analyze the performance of the executive in managing the assets within the Yogyakarta Regional Police. (2) Analyzing the environmental asset management in the Yogyakarta Regional Police with IPA analysis. (3) To formulate strategies in the optimization of asset management at the Yogyakarta Regional Police. In studies using 2 (two) data analysis tools that IPA (Importance Performance Analysis) and SWOT by (1) analysis of EFAS (external strategic factors analysis summary), (2) IFAS (Internal strategic factors analysis summary) analysis. Based on the analysis concluded that (1) in the IPA analysis of attributes that are in quadrant A or who should get top priority is item number 7: Assets have been defined uses and purposes. Other attributes that are in quadrant B or maintain performance. (2) Strength and opportunities of asset management in the Yogyakarta police are: (a) The legal status of a benefit, (b) Completion of data base of assets, (c) Inventory of assets increases the optimization and utilization, (d) The process of legal audit unclear ownership status, (e) Data analysis of data assets, (f) Legal Audit carried out with good assets. (2) weakness and barriers in Yogyakarta Regional Police asset management include: (a) Inventory of assets conducted by a specialized agency dealing with assets, (b) The process of asset identification, (c) The assessment of the assets of the Yogyakarta Regional Police, (d) Data asset base in an up-to-date, (f) Inventory asset in accordance with the Act